Feasibility study on the forming of amorphous Fe-based alloy powder - See Toh, Beng Sing. (2010)
Amorphous alloy have been of increasing interest due to its superiority in mechanical, corrosion and magnetic properties. Since the feasibility on forming components from amorphous powder is rarely investigated, this study attempts to investigate the forming of Fe-Si-B-Cr amorphous powder via compaction and Spark Plasma Sintering (SPS), a developed rapid sintering technique. To conduct this feasibility study, compaction techniques and parameters are investigated. Hot and cold pressing is first conducted without binder, to avoid additional step of debinding. As amorphous powder particles are small and hard, compaction is difficult and binder is added to improve the green strength. The key findings of this project is that when SPS with pressure is conducted above 450°C, crystallization will occur and sintering effect is significantly improved as a pressure of 80MPa is applied. In addition, sintering with pressure at 350°C shows slight sintering effects while retaining amorphous nature. Although all the processed discs are not sintered, the result suggests that if SPS with pressure is conducted below the 450°C, between the Tg (538°C-538°C) and Tx (545°C-548°C) range, combined with a suitable consolidation time, sintered amorphous part can be attained. Therefore, forming of Fe-Si-B-Cr amorphous powder maybe possible.